2016
DOI: 10.5539/jas.v8n3p162
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Fat Content of Fried Potato Pellet Chips Using Carboxymethyl Cellulose and Soy Protein Isolate Solutions as Coating Films

Abstract: The aim of this work was to investigate the influence of different percentages of Carboxymethyl Cellulose (CMC) and Soy Protein Isolate (SPI) as coating material films for potato pellet chips during deep-fat frying on fat uptake, and sensory properties. Coating solutions of 2%, 6%, 10% and 14% w/v were prepared and heated to 90 ºC for 5 minutes then cooled. Samples were dipped in the coating solutions followed by air drying. The treatments were fried and analyzed for fat uptake and moisture retention. Sensoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
(14 reference statements)
4
23
0
2
Order By: Relevance
“…This is related to the secondary characteristics of hydrocolloids that can form a gel layer due to the thermal gelation of hydrocolloids. This result was agreed with the previous report [12], they reported that a low amount of oil absorption was caused by the formation of covalent links within films during heating.…”
Section: ) Fat Contentsupporting
confidence: 94%
See 3 more Smart Citations
“…This is related to the secondary characteristics of hydrocolloids that can form a gel layer due to the thermal gelation of hydrocolloids. This result was agreed with the previous report [12], they reported that a low amount of oil absorption was caused by the formation of covalent links within films during heating.…”
Section: ) Fat Contentsupporting
confidence: 94%
“…These factors will affect the overall acceptance of the panelist's preference levels in the product. According to the previous report, edible coating improves sensory properties of chips, including appearance, color, flavor, taste, crispy that lead to increasing the score of overall acceptability [12].…”
Section: ) Colourmentioning
confidence: 99%
See 2 more Smart Citations
“…Se ha señalado que la naturaleza del recubrimiento es importante, ya que durante el proceso térmico éstos se podrían degradar con mayor facilidad y por lo tanto, alterar la grasa de fritura en cuanto a su viscosidad y propiedades químicas, formando componentes tóxicos, los cuales podrían aglutinarse en la costra de los productos y ser consumidos (Pedreschi et al 2014;Angor 2016;Khazaei et al 2016). Por ello, aún se requieren más investigaciones que ayuden a optimizar las condiciones reales de procesamiento.…”
Section: …………………………………………………………………………………………………… Introducción:-unclassified